„Katalog osób rozpracowywanych IPN-KŚZpNP jako źródło do badań nad dziejami NSZZ „Solidarność”: szanse i słabości” - Żukowski , Marcin (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article concerns one of the directories of the Institute of National Remembrance - the list of persons persecuted by the communist security authorities. The author introduces a method for creating a directory, its strengths and weaknesses. It stresses the importance of such work and suggests some changes. This innovative text which is to show the achievements of the Institute of National Remembrance in the work of the Polish political opposition from the 80s.